2011
DOI: 10.1111/j.1365-2125.2010.03827.x
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin‐associated bleeding events and concomitant use of potentially interacting medicines reported to the Norwegian spontaneous reporting system

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Bleeding is the main adverse drug reaction of warfarin use. • Several medicines, herbal products and dietary supplements may interact with warfarin. • A high percentage of patients on warfarin receive potentially interacting substances. WHAT THIS STUDY ADDS • Potentially interacting medicines were used in more than 50% of the warfarin‐associated bleeding events reported to the Norwegian spontaneous reporting system. • Only a minority of the concomitant medicines we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
4
15
1
Order By: Relevance
“…The finding of this study is consistent with previous studies [26-29]. One analysis in Norway showed that heparin, antibacterial and NSAIDs were common interacting drugs [26].…”
Section: Discussionsupporting
confidence: 93%
“…The finding of this study is consistent with previous studies [26-29]. One analysis in Norway showed that heparin, antibacterial and NSAIDs were common interacting drugs [26].…”
Section: Discussionsupporting
confidence: 93%
“…The same authors, using the same methodology, but including new users of phenprocoumone or acenocoumarol, subsequently identified the main comedications associated with major bleeding episodes during anticoagulant therapy as antibacterial drugs, NSAIDs, antithrombotic drugs and tramadol [58]. In a study based on the Norwegian spontaneous reporting system, data on warfarin-associated bleeding events (n0289) as a consequence of drug interaction were detected in more than 50 % of the cases involving antibacterials, NSAIDs/COX-2 inhibitors and heparins [59]. These results are also in accordance with our study.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for this is the variety of interactions (about 400) with other drugs 12,13. Recent data suggest that warfarin drug interactions might be a major source of the bleeding events in patients receiving anticoagulant treatment 14. Warfarin interactions can vary from theoretical (clinically insignificant) to severe life-threatening interactions.…”
Section: Introductionmentioning
confidence: 99%